Dynamic pedestrian lighting: Effects on walking speed, legibility and environmental perception. (June 2018) - Pedersen, E; Johansson, M
LED technology provides new opportunities to change the illuminance on pedestrian pathways in response to the presence of people. This study explores possible effects of dimming as such on walking, legibility and perception. In an indoor full-scale laboratory, 61 participants walked along a 19-m pathway with a motion-detection sensor 10 m before an LED luminaire. The participants walked significantly slower under dimmed than static lighting conditions, even after the illuminance had increased. Legibility decreased with the extent of dimming. The larger the difference in illuminance between dimmed and full light, the stronger the self-reported reaction. The results indicate that changes in illuminance affect walking, and that legibility and perception are affected by the overall lighting design of pedestrian pathways rather than by dimming as such.